Association of cardiovascular health with reproductive lifespan and pregnancy loss: insights from NHANES 2005–2018 - Yan, Yang; Chen, Jiajia; Qin, Jinlong; Yu, Min; Du, Meirong (Frontiers in Endocrinology, 2025)
BackgroundAltered reproductive timing of females has close relations to long-term health. Since the cardiovascular system delivers oxygen, nutrients, and hormones throughout the body, cardiovascular health (CVH) may significantly impact hormonally controlled events such as pregnancy, menarche, and menopause. This study sought to determine whether CVH is associated with reproductive lifespan and pregnancy loss, and the mediating role of inflammation.MethodsFemale participants (3964) from the National Health and Nutrition Examination Survey (NHANES) 2005–2018 were employed in this cross-sectional investigation. The Life’s Essential 8 (LE8) score was categorized into low (<50), moderate (50–79), and high (≥80) CVH. The years between menarche and menopause age was computed as the reproductive lifespan. Pregnancy loss was determined by the discrepancy between the total number of pregnancies and the number of live births. We conducted multivariable linear regression models and zero-inflated negative binomial regression models to investigate the prospective association of CVH with reproductive lifespan and pregnancy loss while accounting for various potential confounders. Mediation analysis was applied to explore the function of inflammation.ResultsAfter multivariate adjustment, higher CVH levels were notably associated with lower reproductive lifespan (β=−0.32, 95% CI: −0.47, −0.17, P<0.001) and lower number of pregnancy losses (β=−0.04, 95% CI: −0.07, −0.01, P=0.012). Specifically, increased CVH levels were associated with increased age at menarche (β=0.14, 95% CI: 0.10, 0.18, P<0.001) and decreased age at menopause (β=−0.18, 95% CI: −0.33, −0.04, P=0.014). Furthermore, a linear correlation was observed between CVH and reproductive lifespan (P<0.001), while the number of pregnancy losses decreased as CVH levels increase within a certain range and approximately presented an L-shaped relationship (P=0.009). Subgroup analyses proved a stronger inverse association between CVH and reproductive lifespan among never-married women (P for interaction<0.001), whereas no significant interaction existed between CVH and pregnancy loss. Inflammation biomarker alkaline phosphatase (ALP) mediated 9.4% of the association between CVH and reproductive lifespan (P=0.048).ConclusionsHigher CVH levels were associated with shorter reproductive lifespan and lower prevalence of pregnancy loss at population level, and inflammation may mediate the association of CVH with reproductive lifespan. Comprehensive management of CVH in women may be vital to safeguard their reproductive health.